The Fall of the Aztec Empire and its Dramatic Consequences - Testi, Dario (Richtmann Publishing, 2011)
This article is an excerpt of a long and extensive work on Castilian and Portuguese geographical discoveries of the XV andXVI centuries. Among the jungles, deserts and snowy peaks of the, nowadays well known, central Mexico, takes place one of the mostinteresting, exciting and dramatic encounter in history. It is the 1519. On one side are the soldiers of Castile, armed with steel, on theother side of a huge cultural and mental barricade are the Aztecs, descendants of proud warriors who shed blood to conquer the Anahuacvalley and that, pouring out, more prepare to lose it. The article tries to summarize the main points of the military campaign known as